Eksplorasi Penerapan Activity Based Costing dalam Evaluasi Profitabilitas Proyek: Studi Kasus pada Perusahaan Jasa Konsultan - Hanin Febriana; Ali Tafriji Biswan; Lidya Primta Surbakti (Jurnal Eksplorasi Akuntansi, 2026)
This study examines cost-setting issues in a consulting company that has not yet implemented an activity-based costing system, resulting in inconsistent project and client profitability as well as unmeasured workload assessments. The study aims to explore how activities, work complexity, and cost-setting practices shape cost structures in consulting service firms and to identify operational issues that affect project cost evaluation. A qualitative approach was employed through in-depth interviews, workflow observations, and the review of internal documents to obtain a detailed understanding of activities, task allocation, fee determination, and the recording of working hours and project documentation. The novelty of this study lies in its effort to understand cost formation practices in consulting firms through the perspectives of activities and cost drivers. Specifically, the study focuses on how activity complexity, variations in workload, and fee-setting practices influence project cost evaluation. The findings indicate that the company frequently handles projects with similar fees but different levels of complexity, resulting in increased work effort without corresponding profit growth. Inaccurate time-recording practices also make it difficult for the company to assess the cost burden of each activity and lead to pricing decisions that are not supported by data. The study concludes that issues such as the mismatch between workload and project fees, inadequate activity recording practices, and unidentified overhead costs highlight the need for a more activity-oriented cost approach. Activity-Based Costing has the potential to serve as a framework for understanding resource consumption and supporting a more structured project cost evaluation process.